İletişim bağlamında Auteur kuramı ve Yeşim Ustaoğlu sineması - Toptaş, Şehriban (My University, 2020)
Andre Bazin ‘in auteur kuramı ile iletişim arasında ilişki kurmaya çalışan bu tez çalışması, bütün kitle iletişim araçları kadar sinemanın da insanları farklı şekillerde etkileyebileceğini, özellikle auteur yönetmenlerin kişisel stilleriyle yaptığı filmlerin bu konuda öncü olduğunu ortaya koymayı amaçlamaktadır. Diğer disiplinlere kıyasla sinema, tarih boyunca popülaritesini hep korumuştur ve zaman içerisinde sürekli gelişmiştir. Anaakım sinemaya tepki olarak ortaya çıkan auteur kuram da bu gelişmelerden biridir. Auteur kurama bağlı yönetmenler stüdyodan uzaklaşıp gerçek mekanlarda gerçek hikayeleri çekerek, birçok kuralı hiçe sayarak kendi stillerini oluşturmuşlardır. Yeşim Ustaoğlu da Türkiye’de auteur kurama bağlı kalarak yaptığı filmlerle, sinemanın insan iletişimi ve toplum içerisindeki önemini gözler önüne sermiştir.

This thesis tries to establish relation between Andre Bazin's auteur theory and communication whilst aiming to reveal that cinema can influence people in different ways as well as all media, especially the films made by auteur directors' personal styles. Compared to other disciplines, cinema has always maintained its popularity throughout history and has evolved over time. Auteur theory is one of these developments that emerged in response to mainstream cinema. In fact, auteur theoretical directors are the pioneers for demonstrating how movies can touch the society in various means since they have moved away from the studio to shoot their own stories in real environments, ignoring many rules to create their own styles. Yesim Ustaoglu as one of these artists adhering to the auteur theory in Turkey, has demonstrated the importance of human communication in cinema and society.
Keywords: Auteur; Cinema; French New Wave; Motion pictures; Motion pictures and television; Sinema; Sinema ve televizyon; Yeni Dalga Auteur; Yesim Ustaoglu; Yeşim Ustaoğlu